(untitled) (European Journal of Pedagogical Initiatives and Educational Practices, 2025)
This article scientifically analyzes the effect of stress on the human body, in particular on the functioning of the immune system. The article discusses psychological and physiological stress factors, their mechanisms of influence on the immune response through the hormonal system. Studies show that long-term or severe stress reduces the activity of immune cells, making the body vulnerable to infectious and chronic diseases. At the same time, it is proven that maintaining a positive psychological state, managing stress, and leading a healthy lifestyle are important factors in strengthening immunity.